Innovation and Its Discontents: Pathways and Barriers in the Diffusion of Assertive Community Treatment - ROCHEFORT, DAVID A. (The Milbank quarterly, 2019)
Context: Originating at the county level in Wisconsin in the early 1970s, Assertive Community Treatment is one of the most influential mental health programs ever developed. The subject of hundreds of research studies and recipient of enthusiastic backing from private advocacy organizations and government agencies, the program has spread widely across the United States and internationally as a package of resources and management techniques for supporting individuals with severe and chronic mental illness in the community. Today, however, ACT is associated with a rising tide of criticism challenging the program's practices and philosophy while alternative service models are advancing. Methods: To trace the history of the Assertive Community Treatment movement, a diffusion-of-innovation framework was applied based on relevant concepts from public policy analysis, organizational behavior, implementation science, and other fields. In-depth review of the literature on ACT design, management, and performance also provided insight into the program's creation and subsequent evolution across different settings. Findings: A number of factors have functioned to fuel and to constrain ACT diffusion. The former category includes policy learning through research; the role of policy entrepreneurs; ACT's acceptance as a normative standard; and a thriving international epistemic community. The latter category includes cost concerns, fidelity demands, shifting norms, research contradictions and gaps, and a multifactorial context affecting program adoption. Currently, the program stands at a crossroads, strained by the principle of adherence to a long-standing operational framework, on the one hand, and calls to adjust to an environment of changing demands and opportunities, on the other. Conclusions: For nearly 50 years, Assertive Community Treatment has been a mainstay of community mental health programming in the United States and other parts of the world. This presence will continue, but not in any static sense. A growing number of hybrid and competing versions of the program are likely to develop to serve specialized clientele groups and to respond to consumer demands and the recovery paradigm in behavioral health care.